Intanpari.App (Unlimited Access to Education): An Online Entrepreneurship Learning Platform to Improve the Entrepreneurial Skills of Youth Human Resources In The Land of Intanpari - Widodo, Zandra Dwanita; Budiana Kurniawati, Susilaningtyas (ProBisnis : Jurnal Manajemen, 2025)
The issue of youth unemployment and the limited access to entrepreneurship education in rural areas forms the background for the conceptual development of Intanpari.app, an online-based entrepreneurship learning platform in Karanganyar Regency. This study employs a qualitative exploratory approach grounded in conceptual study, using data collection techniques that include systematic literature review and exploratory interviews with key informants.The findings indicate an urgent need for the transformation of entrepreneurship education into a more flexible, adaptive, and practice-based digital format. The identified user needs highlight the importance of providing contextual learning modules, virtual collaborative spaces, and simple business planning tools. Based on the analysis, a conceptual framework for Intanpari.app was developed, which is expected to expand access to entrepreneurship education, enhance practical skills among youth, and strengthen the local economic ecosystem. These findings enrich the literature on technology-based entrepreneurship education and provide a direction for further development through prototype creation and field testing.